LOW EMPLOYMENT INTENSITY OF GROWTH AND SPECIFICS OF SLOVAK LABOUR MARKET - Veronika Hvozdíková; Karol Morvay (European Scientific Journal, ESJ, 2015)
This paper aims to explain low employment elasticity of growth in the Slovak Republic as a factor behind some atypical trends that occurred in the Slovak labour market in the pre-crisis period. Lower employment intensity of growth is common in some developing economies overcoming the technology and productivity gap – the idea behind the weak relation between output growth and employment increases in Slovakia is the same, however, the “employment growth threshold” in Slovakia has been remarkably high even when compared to other economies in the region. As a result, the shift towards more flexible working arrangements as well as unusually low wage share (in total income) persisted in the economy before the crisis. The very recent development suggests that the crisis could have created the opportunity to change the nature of economic growth and move towards more labour intensive sectors.